Hubungan Bullying Dengan Kemampuan Sosial Pada Remaja Di SMK X Kota Bandung - Pragholapati, Andria; Muliani, Rizki; Aryanti, Fita Lia (Journal of Research and Measurement in Psychology: JPPP, 2020)
n 2015, 84% of students in Indonesia experienced difficulties in school, one of which is bullying. Most of adolescents in Bandung’s X Vocational School reported that they have been bullied by their peers. It is assumed that one of the factors which might contribute in bullying is the lack of social abilities. This study aims to find the relationship between bullying and social abilities among adolescents in X Vocational School in Bandung, West Java. This is a descriptive research using cross-sectional design. Eighty-three participants were selected as the sample of the study using purposive sampling technique. Multidimensional Peer-Victimization Scale Questionnaire were used to assess bullying and Social Skills Rating System (SSRS) to measure social ability. Spearman-rank Correlation was performed. This study reports most adolescents have high rates of bullying (88%) and moderate level of social abilities (56.6%). Statistical test result shows that there is a significant correlation between intimidation and social ability (r=0.249; p-value=0.023). It is concluded that a weak relationship between intimidation and social ability were reported. It is suggested to SMK X for paying attention to their students and providing counselling services